Alunos com deficiência física em práticas esportivas na escola - PINHEIRO, Danielle dos Prazeres (2025)
This article presents an analysis of the difficulties and strategies, in the school environment, to assist children with physical disabilities in sports activities; this work is justified from a personal concern about the subject, since I have already encountered this difficulty in the family environment. In this way, I used documentary research, where five texts were selected from an event called the Brazilian Congress of Special Education (CBEE), with the general objective of analyzing the process of school inclusion and curricular strategies with children with physical disabilities in sports practices in schools, and the specific ones: to evaluate the pedagogical strategies that are contemplated in the scope of school planning (PPP) for the inclusion of physically disabled students in sports practices, to verify what strategies are used to include the physically disabled in actions aimed at sports practices and to reflect what methods are used by the physical education teacher in their classes to include the physically disabled student in the activities. This research is qualitative in nature, so we relied on some theoretical contributions from Glat and Blanco (2007), Sassaki (1998) and others. As a result, we observed that many strategies are being taken, such as adapting materials, but this is still insufficient, as the discussion on inclusion is still only discussed in educational environments, making it difficult for the community to have access to this knowledge.